Late Relapse of Previous Pulmonary Cryptococcosis With Symptoms Resembling Cerebral Infarction: A Case Report - Anatoli Pinchuk; Gernot Geginat; Volker Rickerts; Belal Neyazi; Klaus Peter Stein; Christian Mawrin; I. Erol Sandalcioglu; Ali Rashidi (Case Reports in Infectious Diseases)
Cryptococcosis, an infection caused by Cryptococcus neoformans and Cryptococcus gattii, predominantly targets the central nervous system (CNS) in patients with AIDS but is not limited to this group. The disease can also occur in individuals with various immunosuppressive conditions, frequently involving the brain or lungs. Cryptococcal meningitis (CM) is the most common form of fungal meningoencephalitis, leading to intracerebral infections, cerebral infarction, or hydrocephalus. The clinical presentation of CM is nonspecific, and imaging features can vary significantly. This case report presents a patient with cerebral infarction, who was HIV-negative but had been on long-term cortisone therapy. Notably, the patient had a history of pulmonary cryptococcosis 15 years prior to cerebral involvement. When initially at our clinic, histology and culture results from brain biopsies were negative and the earlier pulmonary cryptococcosis history was unknown. Subsequently, cryptococcal antigen was detected in both serum and cerebrospinal fluid (CSF), and C. neoformans was cultivated from CSF. This case highlights the critical importance of maintaining a high index of suspicion for CM, particularly in patients with a history of previous cryptococcal infections, and it also demonstrates the possibility of false-negative brain biopsy results due to secondary vascular events associated with CM.